Utilização de duas alturas de resíduo no manejo de cultivares de Urochloa sp. e associações de feno de gliricidia e subproduto de acerola na qualidade das silagens - SILVA, Eduarda Castro da (2024)
The introduction of new hybrids is essential to increase productivity, ensure adaptability to different soil and climate conditions and improve nutritional value, thus, increasing animal performance. The objective was to evaluate the morphogenic characteristics,structural and chemical characteristics of five cultivars of the genus brachiaria with a 5x2 factorial in randomized blocks for two consecutive years. The cultivars used were: Brachiaria hybrid cv. Cayana, Sabiá and Mulato II, Brachiaria brizantha cv. Marandu and Piatã, combined with two residue heights 20 and 25 cm, in addition, the silage of the Cayana and Sabiá grass with the inclusion of acerola by-product and gliricidia hay, respectively, in chemical composition, microbiological profile and aerobic stability of silage. An effect was observed between cultivars for total forage production with greater increase in leaves and dead material for hybrid species, in a similar way the following year, there was a difference in total forage production, but the increase significant was the stalk production with an effect on the leaf/stalk ratio, while for the production of dead material, the residual height was greater than 20 cm. There was difference in height in the two years of evaluation, but tiller density was significant only for the second year, with hybrid species standing out. Observed interaction effect for number of leaves and phyllochron and isolated effect of cultivars for leaf elongation and leaf lifespan, however, in the following year only stem elongation was significant. Lowest tiller survival rate was found for Piatã during the first year of evaluation. For the composition chemistry in both years, there was an effect on dry matter, organic matter, ash, crude protein and neutral detergent fiber, however only in the following year there was for acid detergent fiber and hemicellulose. In the quality of silages, the inclusion of gliricidia hay linearly increased the production of dry matter, crude protein and mold population, while for neutral detergent fiber, hemicellulose and of yeast there was a quadratic effect, for the inclusion of the acerola by-product there was positive linear effect for DM contents, presenting a quadratic effect only for the mold population. The cultivars Sábia Mulato II and Cayana presented characteristics positive and assertive for establishment in the region with high leaf/stem ratio and tiller density attributed to the potential for leaf production, presenting similarities to the brizantha Marandu species. While, for silages, the acerola by-product increased the dry matter content, while gliricidia hay provided higher percentages of buta protein and reduced detergent fiber neutral, therefore, it is recommended to include 20% of the gliricidia hay and 10% of the residue of acerola.